Kinetic analysis of partial decomposition of starch in hot-compressed water - Ueno, S.(Niigata Univ. of Pharmacy and Applied Life Sciences (Japan)); Anzai, M; Shigematsu, T; Fujii, T (Japan Journal of Food Engineering, 2008)
The partial decomposition reaction of starch in hot-compressed water was studied using a tubular reactor at 160-210degC and 25-45 MPa. The increase rate of reducing sugar concentrations at short residence times was considered as initial reaction rate of partial decomposition. The kinetic analysis of the initial reaction rate indicated that the reaction mechanism over 190degC was different from that below 180degC. The reaction mechanism over 190degC could be expressed by bimolecular reaction between starch and ionized water. The activation energies for starch partial decomposition were about 120 kJ/mol, which was almost the same as the activation energies of maltose and isomaltose hydrolysis. The activation volumes were equivalent to the volume of a few water molecules, suggesting that the reaction proceeded like the gas phase reactions. In contrast, the reaction mechanism below 180degC could be expressed by multimolecular reaction. The activation volumes were significantly larger than those over 190degC. The large activation volume below 180degC suggested that the reaction proceeded, like the liquid phase reactions, with solvent effect between starch and multiple water molecules.